Chemosensory sensitivity reflects reproductive status in the ant Harpegnathos saltator - Majid Ghaninia (Nature Portfolio, 2017)
Abstract Insects communicate with pheromones using sensitive antennal sensilla. Although trace amounts of pheromones can be detected by many insects, context-dependent increased costs of high sensitivity might lead to plasticity in sensillum responsiveness. We have functionally characterized basiconic sensilla of the ant Harpegnathos saltator for responses to general odors in comparison to cuticular hydrocarbons which can act as fertility signals emitted by the principal reproductive(s) of a colony to inhibit reproduction by worker colony members. When released from inhibition workers may become reproductive gamergates. We observed plasticity in olfactory sensitivity after transition to reproductive status with significant reductions in electrophysiological responses to several long-chained cuticular hydrocarbons. Although gamergates lived on average five times longer than non-reproductive workers, the shift to reproductive status rather than age differences matched the pattern of changes in olfactory sensitivity. Decreasing sensillum responsiveness to cuticular hydrocarbons could potentially reduce mutually inhibitory or self-inhibitory effects on gamergate reproduction.